Biocatalytic Performance and Dosage-Dependent Behavior of Fruit Peel–Derived Eco-Enzymes in Organic Matter Removal from Simulated Lake Water - Aldho Pramana Putra; Puti Sri Komala; Ansiha Nur (Jurnal Riset Kimia, 2026)
The increasing organic pollution in lake water systems due to continuous domestic wastewater discharge presents significant environmental challenges, particularly in urban areas. This study investigates the biocatalytic performance and dosage-dependent behavior of fruit peel–derived eco-enzymes in removing organic matter from simulated lake water under laboratory-scale batch conditions. Eco-enzymes were produced from banana, pineapple, papaya, watermelon, and orange peels, including a mixed formulation, produced through a three-month anaerobic fermentation process. The products were characterized based on physicochemical properties and enzymatic activities, including amylase, protease, and lipase, to evaluate their biocatalytic potential. Batch experiments were conducted using eco-enzyme dosages of 5%, 10%, and 15%, with continuous monitoring of chemical oxygen demand (COD) and biochemical oxygen demand (BOD) over 12 days until steady-state conditions were achieved. The results showed that eco-enzymes exhibited significant biocatalytic activity, promoting enzymatic hydrolysis and degradation of complex organic compounds into simpler biodegradable forms. Treatment performance was strongly influenced by dosage, where the 5% concentration achieved the highest removal efficiencies, with maximum reductions of 71.7% for COD and 74.6% for BOD, while higher dosages reduced performance due to additional organic loading. Statistical analysis using one-way ANOVA confirmed that eco-enzyme dosage significantly affected treatment performance, with highly significant differences for COD removal (F = 280.684; p < 0.05) and significant differences for BOD removal (F = 185.117; p < 0.05). The 5% dosage consistently produced the highest kinetic constants for both COD and BOD removal. The highest COD rate constant was obtained with the banana-based eco-enzyme (k = 1.0815 day⁻¹), whereas the highest BOD rate constant was achieved by the pineapple-based eco-enzyme (k = 1.0387 day⁻¹). Higher dosages (10% and 15%) resulted in negative removal efficiencies, suggesting inhibition due to excessive organic loading and preventing meaningful kinetic interpretation. These findings demonstrate the dual role of eco-enzymes as both biocatalytic agents and contributors to organic loading, highlighting the importance of dosage optimization supported by both statistical and kinetic approaches in sustainable lake water remediation systems.